2017
DOI: 10.1038/leu.2017.109
|View full text |Cite
|
Sign up to set email alerts
|

Acute myeloid leukemia in the elderly is characterized by a distinct genetic and epigenetic landscape

Abstract: We stumble on a mystery and embrace it. We investigate and we doubt, but it would be ignorance to believe the inexplicable is impossible.In the end, our reward is a story worth telling. One that not only contributes to knowledge but also transforms us.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 155 publications
5
56
0
Order By: Relevance
“…We speculate that the reasons for the differences include the different number and age distribution of patients and possible ethnic differences among these cohorts (Supporting Information, Table S4). In accordance with previous studies, we also found that SF3B1 , ASXL1 , TET2 , and TP53 more frequently occurred in older patients rather than in younger patients. Recently, three genetic studies of large populations have revealed that somatic mutations in hematopoietic cells leading to clonal expansion are commonly acquired during human aging .…”
Section: Discussionsupporting
confidence: 93%
“…We speculate that the reasons for the differences include the different number and age distribution of patients and possible ethnic differences among these cohorts (Supporting Information, Table S4). In accordance with previous studies, we also found that SF3B1 , ASXL1 , TET2 , and TP53 more frequently occurred in older patients rather than in younger patients. Recently, three genetic studies of large populations have revealed that somatic mutations in hematopoietic cells leading to clonal expansion are commonly acquired during human aging .…”
Section: Discussionsupporting
confidence: 93%
“…22 In a recent study of elderly patients with acute myeloid leukemia, genes in the spliceosomal complex as well as TET2 were found to be altered more frequently than in younger cases, similar to what is seen in MDS. 23 While there are marked differences in the mutational spectrum between early onset MDS and MDS patients diagnosed at a traditional age, overall our results suggest that patients with MDS ≤50 years old constitute part of a continuum rather than a specific group with a distinct molecular pathogenesis. Increased frequency of TET2 mutations parallels the trend seen in healthy controls 17,20 with increasing frequency of TET2 mutations with aging suggesting a disease-initiating role of these mutations in MDS that is consistent with increased MDS risk in asymptomatic mutant carriers.…”
Section: Discussionmentioning
confidence: 54%
“…Previous data indicate that the frequency of acquired somatic mutations increases with age (Silva et al , ; Li et al , ). To adjust for this, we compared clinical and laboratory variables and results of next generation sequencing (NGS) in these 59 patients with 236 age‐matched controls with MDS‐EB2 without Auer rods.…”
Section: Clinical and Laboratory Characteristics Of Mds‐eb2 Patients mentioning
confidence: 94%